2019
DOI: 10.1016/j.commatsci.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The inherent behavior of graphene flakes in water: A molecular dynamics study

Abstract: Graphene-water interaction has been under scrutiny ever since graphene discovery and realization of its exceptional properties. Several computational and experimental reports exist that have tried to look into the interactions involved, however, none of them addresses the issue in its entirety. Most computational analysis doesn't go beyond the atomistic scale and report graphene to be hydrophobic. Meanwhile, several experimental and molecular dynamics (MD) studies show an active interaction between graphene an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…We used TIP4P potential for water (H 2 O) [49], and Lennard-Jones type of pair potential for C and H 2 O interactions [50]. We used TIP4P potential before for water modeling [3,37], and our computational results were in good agreement with the experimental findings [3]. The methodology of Phase I is summarized in the 'Wrinkle Evolution' part of the flow-chart shown in Figure 3.…”
Section: Molecular Dynamics (Md)mentioning
confidence: 72%
See 1 more Smart Citation
“…We used TIP4P potential for water (H 2 O) [49], and Lennard-Jones type of pair potential for C and H 2 O interactions [50]. We used TIP4P potential before for water modeling [3,37], and our computational results were in good agreement with the experimental findings [3]. The methodology of Phase I is summarized in the 'Wrinkle Evolution' part of the flow-chart shown in Figure 3.…”
Section: Molecular Dynamics (Md)mentioning
confidence: 72%
“…The self-folding mechanics of surface wettability on patterned graphene nanoribbons by water evaporation was studied by Zhang et al [36]. We also investigated the interaction of graphene nanoribbons with water droplets [3,37]. The effect of diffused hydrogen molecules in between graphene and copper substrate on the size of wrinkle formation was studied by Wang et al [38].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that water molecules do not strongly bind to a graphene sheet [190]. However, it is still controversial that whether graphene is hydrophobic or hydrophilic, but some experimental reports show that the initial process of producing graphene is reflected that the graphene sheet is hydrophobic or hydrophilic [191]. Some reports showed a changeable behavior of graphene hydrophobicity to hydrophilicity by using chemical additives or ultraviolet radiation [115,192].For instance a combination of acetone and water as a solvent shows a wide range of water contact angles on the graphene surface due to chemisorption of acetone on graphene in any defects of graphene surface [192].…”
Section: Wetting Behavior and Transparency Of Graphenementioning
confidence: 99%